Direct comparison of the aging and memory effects of magnetic nanoclusters and nanoparticles - Sankar, C. Raj; Vijayanand, S.; Verma, Seema; Joy, Pattayil Alias (Solid State Communications, 2007)
The magnetic characteristics of a dense magnetic nanoparticle system and a spin glass system consisting of magnetic nanoclusters are compared. Zero field cooled and field cooled magnetization measurements, including aging and memory experiments, of the nanoparticle and the magnetic cluster systems show similar characteristics, suggesting a common origin for the spin glass-type behavior of the magnetic nanoparticle and nanocluster systems. (C) 2006 Published by Elsevier Ltd.
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses

Ferromagnetic to spin glass cross over in (La,Tb)(2/3)Ca1/3MnO3 - Sankar, C. Raj; Vijayanand, S.; Joy, Pattayil Alias (Solid State Sciences, 2009)
In the series La2/3-xTbxCa1/3MnO3, it is known that the compositions are ferromagnetic for smaller values of x and show spin glass characteristics at larger values of x. Our studies on the magnetic properties of various compositions in the La2/3-xTbxCa1/3MnO3 series show that the cross over from ferromagnetic to spin glass region takes place above x approximate to 1/8. Also, a low temperature anomaly at 30 K, observed in the ac susceptibility curves, disappears for compositions above this critical value of x. A mixed phase region coexists in the narrow compositional range 0.1 <= x <= 0.125, indicating that the ferromagnetic to spin glass cross over is not abrupt. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Ferromagnetism; Magnetic clusters; Manganites; perovskite; Spin glass